Evaluation of Advanced Potato clones for Plant and YIELD CHARACTERS at High hills of nepal - Luitel, Binod P; Khatri, Bhim B; Choudhary, Duryodhan; Kadian, Mohinder S; Arya, Sushma; Bonierbale, Merideth (Potato Journal, 2017)
This experiment was conducted to investigate the performance of advanced potato clones at high hills of Nepal during 2013-2014. Eight advanced potato clones were evaluated with locally adapted variety ‘Lady Rosita’ at Nigaley Farm of Sindhupalchowk and farmers’ field of Dolakha, as an on-station and on-farm experiments, respectively. The plant morphological, late blight disease, and yield characters of potato clones were studied in the both years. CIP 393073.179 and CIP 395112.32 were found resistant to late blight disease in both years. Total tuber number/plant, and marketable yield (t/ha) were highly significant (P≤0.01) among the clones. CIP 395112.32 produced the highest marketable tuber yield (18.5 t/ha) followed by CIP 393073.179 (16.5 t/ha) in on-station and on-farm trials in both years. Clone CIP 395112.32 possessed late blight resistance and better yield, and acceptable rank of tuber appearance, taste and texture as compared to other clones. CIP 395112.32 is recommended to scaleup for farmers in potato cultivation. The adoption of this clone as variety will increase the potato production and improve the food, and nutritional security in project targeted areas.